2016
DOI: 10.3389/fpls.2016.00351
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, Anatomical and Metabolic Implications of Salt Tolerance in the Halophyte Salvadora persica under Hydroponic Culture Condition

Abstract: Salt tolerance mechanism of an extreme halophyte Salvadora persica was assessed by analyzing growth, nutrient uptake, anatomical modifications and alterations in levels of some organic metabolites in seedlings imposed to various levels of salinity (0, 250, 500, and 750 mM NaCl) under hydroponic culture condition. After 21 days of salt treatment, plant height, leaf area, and shoot biomass decreased with increase in salinity whereas the leaf succulence increased significantly with increasing salinity in S. persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
44
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 73 publications
10
44
2
Order By: Relevance
“…Also, they suggested that alteration of mineral uptake from SA applications may be one of the mechanisms for alleviation of salt stress, and positively affected K+/Na+ ratio. Similar explanation was reported by Parida et al, (2016). Also, War et al, (2011) concluded that SA plays an important role in induction of plant defensive system against a variety of biotic and abiotic stresses.…”
Section: Resultssupporting
confidence: 64%
“…Also, they suggested that alteration of mineral uptake from SA applications may be one of the mechanisms for alleviation of salt stress, and positively affected K+/Na+ ratio. Similar explanation was reported by Parida et al, (2016). Also, War et al, (2011) concluded that SA plays an important role in induction of plant defensive system against a variety of biotic and abiotic stresses.…”
Section: Resultssupporting
confidence: 64%
“…In agreement with previous studies, 75-100 % seawater caused a yield reduction in Salicornia persica, Sarcocornia fructicosa and Helianthus tuberosus L. (Zhao et al 2008;Ventura et al 2011); our studies also demonstrated that Salvadora dry matter yield was decreased at 100 % seawater compared to low concentration of seawater (Table 1); however, still this yield was higher than control treatment (0 % seawater) because highest EC of soil in present study was 2.43 dS m -1 which was lower than that of 6.1 dS m -1 where Salvadora exhibited a reduction in growth (Ramoliya et al 2004). Salvadora tolerate the salinity by maintaining osmotic balance and ion homeostasis (Parida et al 2016). Salinityinduced higher accumulation of organic metabolites such as amino acids, reducing sugars and polyphenols was observed (Parida et al 2016).…”
Section: Resultscontrasting
confidence: 45%
“…Salvadora tolerate the salinity by maintaining osmotic balance and ion homeostasis (Parida et al 2016). Salinityinduced higher accumulation of organic metabolites such as amino acids, reducing sugars and polyphenols was observed (Parida et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Gas exchange between the atmosphere and the photosynthetically active mesophyll cells is a key aspect and depends on properties of the cuticle, stomatal conductance and mesophyll conductance [106]. Stomatal density and pore area (long-term adaptation, no longer influenced in fully expanded leaves) and the regulation of stomatal opening (reversible short-term adaptation) are highly important for the control of stomatal transpiration and water use efficiency in drought-stressed plants [107][108][109][110]. A reduced stomatal density in halophytes exposed to salt stress (compared to unstressed control plants) was reported by several groups [107][108][109][110] and such adaptations were also considered for selecting/breeding crop varieties with improved abiotic stress tolerance by "learning from halophytes" [109].…”
Section: Leaf Morphology and Physiologymentioning
confidence: 99%
“…Stomatal density and pore area (long-term adaptation, no longer influenced in fully expanded leaves) and the regulation of stomatal opening (reversible short-term adaptation) are highly important for the control of stomatal transpiration and water use efficiency in drought-stressed plants [107][108][109][110]. A reduced stomatal density in halophytes exposed to salt stress (compared to unstressed control plants) was reported by several groups [107][108][109][110] and such adaptations were also considered for selecting/breeding crop varieties with improved abiotic stress tolerance by "learning from halophytes" [109]. Besides the morphological adaptations in drought-exposed leaves, other important mechanisms are based on changes in the protein pattern (e.g., accumulation of chaperonins or increased activities of enzymes involved in the detoxification of reactive oxygen species or the production of compatible solutes [18,103].…”
Section: Leaf Morphology and Physiologymentioning
confidence: 99%